Analisis Hubungan Kadar Hemoglobin dengan Status Gizi pada Pasien Hemodialisis di Rumah Sakit Umum Daerah Sleman - Wijayanti, Dian; Siwi Tri Nugroho Heni, Maya; Bella Grace Gabriella Azzahra, Asiyah; Safira, Nabilla (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Anemia and malnutrition are common complications in hemodialysis patients that can impact prognosis and quality of life. This study aimed to analyze the relationship between hemoglobin levels and nutritional status in regular hemodialysis patients at Sleman Regional General Hospital. This observational study used a cross-sectional design and was conducted in July 2024 using the total sampling method. The study subjects consisted of 117 regular hemodialysis patients who met the inclusion criteria: aged ≥18 years and undergoing routine hemodialysis at least twice a week. Data collection included demographic characteristics, hemoglobin levels from laboratory results, and anthropometric measurements to calculate Body Mass Index (BMI). Data analysis was performed using the chi-square test. The results showed that the average hemoglobin level of patients was 8.80 g/dL (SD ± 1.79), with 28.21% falling into the sufficient category (8.10–9.00 g/dL). Nutritional status assessment revealed diverse conditions among patients, with 52.14% having normal nutritional status based on BMI calculations (mean 24.31 ± 4.26 kg/m²), while 12.82% were underweight, and 35.04% were classified as overweight/obese. Statistical analysis indicated no significant relationship between hemoglobin levels and nutritional status (p = 0.997, r = -0.052), suggesting that these parameters are independently influenced by different factors. The conclusion of this study emphasizes the importance of a comprehensive and individualized approach in managing hemodialysis patients, particularly focusing on anemia treatment through ESA administration and iron supplementation. Additionally, regular monitoring of nutritional status using more accurate methods such as Bioimpedance Spectroscopy (BIS) is recommended to ensure optimal patient care and improved outcomes.